Attending to Race (or Gender) Does Not Increase Race (or Gender) Aftereffects - Davidenko, Nicolas; Vu, Chan Q.; Heller, Nathan H.; Collins, John M. (Frontiers in Psychology, 2016)
Recent research has shown that attention can influence the strength of face aftereffects. For example attending to changes in facial features increases the strength of identity and figural aftereffects relative to passive viewing (Rhodes et al., 2011). Here we ask whether attending to a specific social dimension of a face (such as race or gender) influences the strength of face aftereffects along that dimension. Across three experiments, participants completed many single-shot face adaptation trials. In each trial, participants observed a computer-generated adapting face for 5 seconds while instructed to focus on either the race or gender of that adapting face. Adapting faces were either Asian and female or Caucasian and male. In Experiment 1, all trials included an intermediate question following each adaptation period, soliciting a rating of the adapting face on the attended dimension (e.g. race). In Experiment 2 only half of the trials included this intermediate question, and in Experiment 3 only a quarter of the trials did. In all three experiments, participants were subsequently presented with a race- and gender-neutral face and asked to rate it on either the attended dimension (e.g. race; attention-congruent trials) or the unattended dimension (e.g. gender; attention-incongruent trials) using a 7-point scale. Overall, participants showed significant aftereffects in all conditions, manifesting as (1) higher Asian ratings of the neutral faces following Caucasian vs. Asian adapting faces and (2) higher female ratings of neutral faces following male vs. female adapting faces. Intriguingly, although reaction times were shorter during attention-congruent vs. attention-incongruent trials, aftereffects were no stronger along attention-congruent than attention-incongruent dimensions. Our results suggest that attending to a facial dimension like race or gender does not result in increased adaptation to that dimension.